2018
DOI: 10.1590/1678-7757-2017-0172
|View full text |Cite
|
Sign up to set email alerts
|

Osteoradionecrosis of the jaws: case series treated with adjuvant low-level laser therapy and antimicrobial photodynamic therapy

Abstract: Background:Osteoradionecrosis of the jaw (ORNJ) is the most severe and complex sequel of head and neck radiotherapy (RT) because of the bone involved, it may cause pain, paresthesia, foul odor, fistulae with suppuration, need for extra oral communication and pathological fracture. We treated twenty lesions of ORNJ using low-level laser therapy (LLLT) and antimicrobial photodynamic therapy (aPDT). The objective of this study was to stimulate the affected area to homeostasis and to promote the healing of the ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 29 publications
0
26
0
9
Order By: Relevance
“…The only LLLT report found in our review dated back to 2018 ( 24 ). The effectiveness of LLLT is supported by studies in which its effects on the healing process of the oral mucosa are highlighted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only LLLT report found in our review dated back to 2018 ( 24 ). The effectiveness of LLLT is supported by studies in which its effects on the healing process of the oral mucosa are highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…All of these treatments were guided mainly by Marx's theory ( 9 ). More recently and in light of the pathophysiology of the disease proposed by Delanian ( 20 ), pharmacological treatment with pentoxifylline-tocopherol with or without clodronate (PENTOCLO) ( 22 ), teriparatide ( 23 ) and low-level laser therapy (LLLT) ( 24 ) have been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…A laserterapia, além de poder ser utilizada para acelerar a osseointegração e a cicatrização de tecidos moles, é um excelente aliado contra a peri-implantite, de forma que reduz a microflora bacteriana, com isso, diminui a agressão dos agentes patológicos sobre o periodonto (HESSLING et al, 2015;NOBA et al, 2018). Ribeiro et al (2018), em seu estudo, observou resultados imediatos após as sessões iniciais.…”
Section: Implantes Dentários Em Pacientes Irradiadosunclassified
“…A recent retrospective study showed the combined use of low-power laser (Therapy XT-diode laser at 660 nm and 808 nm, DMC Group) with PDT led to remission of ORN and repair of mucosal damage. 27 However, studies evaluating this treatment modality are limited in the current literature, and its reproducibility remains to be seen.…”
Section: Alternative Treatment Modalitiesmentioning
confidence: 99%